Konsep Perkembangan Psikologi Kepribadian Pada Manusia - Irqon, Ade M; Setiawan , Irawan; Abdullah, Ahmad; Sukatin (MUNTAZAM, 2023)
This study aims to explain the concept of the development of personality psychology in humans. Research using literature studies. The results explain that personality is the part of the psyche that builds human existence into a single whole, not divided in functions. Understanding personality means understanding me, self, self or understanding the whole person. Sigmund Freud explained that there are three elements in the structure of personality, namely the id, ego, and super ego. Personality according to Islamic psychology is the integration of the system of human heart, reason, and passions that give rise to behavior. The nafsani aspect of man has three potentials, namely: (1) qalbu (divine nature) as a supra-conscious aspect of man that has emotional power (rasa); (2) reason (human nature) as an aspect of human consciousness that has cognition (creation); (3) Lust (fitrah hayawaniyah) as a pre or lower aspect of human consciousness that has conation power (karsa). There are three personality dynamics in the Islamic perspective, namely the personality of ammarah (nafsalammarah), the personality of lawwamah (nafsal-lawwamah), the personality of muthmainnah (nafsal-muthmainnah). While the factors that make up personality are divided into three streams, namely Empiricism, Nativism and Convergence.